Improving Children's Body Balance Through Playing on the Balance Board at PAUD Waazrim in Lebong Regency - Febi Melati; Mimpira Haryono; Ela Pebriani (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aimed to improve the body balance ability of children aged 4–5 years through balance board play activities at PAUD Waazrim, Lebong Regency. The study employed a Classroom Action Research (CAR) method using the John Elliott model, conducted in two cycles with 15 children as the research subjects. Data were collected through observation and documentation, while data analysis was carried out using descriptive quantitative techniques with percentage calculations. The results showed that children's body balance ability increased from 66.67% in Cycle I to 86.67% in Cycle II. The percentage achieved in Cycle II was categorized as Very Well Developed (VWD). Therefore, balance board play activities were proven to be effective in improving the body balance ability of children aged 4–5 years at PAUD Waazrim, Lebong Regency.